Perennialisme dan Moderasi Beragama sebagai Pilar Strategis Kerukunan di Tengah Intoleransi Beragama di Indonesia - Zulkarnain, Zulkarnain; Gule, Yosefo (Jurnal Penelitian Agama Hindu, 2025)
Religious intolerance in Indonesia has been on the rise, negatively affecting social harmony through increasing violations of religious freedom by both state and non-state actors. This phenomenon underscores the need for an approach capable of addressing the complexities of a multi-religious society. This study aims to analyze the contributions of perennialism and religious moderation as strategic pillars in fostering harmony amidst religious intolerance, while also contributing to the fields of religious studies and social-religious policy in Indonesia. The study adopts a qualitative literature review methodology, utilizing thematic analysis of relevant literature. The thematic analysis is carried out by identifying the key themes in the literature on perennialism, religious moderation, and interfaith harmony, and examining how these concepts are applied in the Indonesian context. The findings indicate that perennialism provides a philosophical foundation through the recognition of universal spiritual values shared across religions, while religious moderation promotes inclusive and tolerant attitudes in religious practices. Together, these concepts serve as strategic pillars in strengthening interfaith dialogue, fostering solidarity, and enhancing cross-cultural understanding. Additionally, religious moderation emphasizes the importance of Pancasila values as the foundation of national unity. In conclusion, the integration of perennialism and religious moderation offers not only theoretical insights but also practical solutions to mitigate religious conflict and build sustainable harmony in Indonesia's multicultural society. This study introduces a novel approach by integrating perennialism and religious moderation, offering a more holistic and contextually relevant framework for Indonesia’s socio-religious landscape, an area not extensively addressed in prior research.